Teks Geguritan Padem Warak Analisis Bentuk, Fungsi, dan Makna - Bayu Mutra Wibawa, I Putu (Humanis; Volume 15. No.2. Mei 2016, 2016)
Research on ink Geguritan Padem Warak text discusses the analysis of form, function and meaning. This analysis had the obejective to describe the form and describe the function and meaning contained in the text Geguritan Padem Warak.This study uses the structural theory, functions, and semiotics.  Structural theory based on the theory of Wellek and Werren, using the function theory of Damono theory, the theory of semiotics and semiotic use of Charles Sanders Peirce. Methods and techniques used divided into three stages, namely (1) the stage of the provision of data by using methods refer and the techniques used is the techniques of recording, and assisted with translation techniques (2) the stage of data analysis, using qualitative methods anf techniques used are descriptive technique analytic, and (3) the stage of data analysis using formal methods informally assisted with deductive and inductive techniques. Disclosure of a structure that builds good Geguritan Padem Warak text form, content, function and meaning cotained therein.Form in this study include, code language and literature, styke and variety of language. Contents include beginning, middle, and end.  Functions contained therein, is the function of religious, social, and magical function. And meanings contained therein, such as harmony anf maligia.
Keywords: shape, function and meaning